PELATIHAN KESOPANAN BERBAHASA SISWA SD BERBASIS KARYA SASTRA DI PERUMAHAN CITRA BUNGO PASANG KELURAHAN SUNGAI TARUNG KECAMATAN KOTO TANGAH PADANG - Aruna Laila; Wahyudi Rahmat; Samsiarni Samsiarni (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
Politeness in language is a soft skill that needs to be instilled in children, especially elementary schools, because the times and technological advancements require soft skills of the younger generation to develop. As a result, many children have ethics that are far from what parents and their environment want. For this problem, this reason is used as a form of coping or a way of giving attention to elementary students so that politeness in language can be maintained well. Partners in this service are PKK mothers who have children at the elementary level who live in the Citra Bungoidal housing complex. With this language courtesy training it is expected that elementary students especially those living in Citra Bungo Pasang housing will have the modesty of language in their daily lives. The language politeness of elementary school students is expected to be not only polite to parents, but also to friends, and others who are the opponents. Based on the partner's problem, the proposed solution will be implemented in two stages, namely, the first stage by providing material on language courtesy, and strategies for speaking to elementary students who live in the Citra Bungo Village housing Sungai Tarung Village, Koto Tangah District. The material is presented using power points and infocus. After the language courtesy material was given to elementary school students living in Citra Bungo Village, Sungai Tarung Subdistrict, Koto Tangah Subdistrict, students were told to interact with their friends and parents. This is done to see whether the student understands and can apply it in communication. The results of the language courtesy training given to elementary school students residing in Citra Bungo Pasang housing were observed two weeks after the material was purchased. The results were very satisfying, because elementary school students residing in the Citra Bungo Pasang housing complex which had often said rudely had changed. Because these elementary students reminded each other not to say rude.